PENANGANAN PEMBIAYAAN BERMASALAH DI BANK SUMSEL BABEL CAPEM MUARA KELINGI - Sanjaya, Ican; Ni’mati Rahmatika, Arivatu (Izdihar: Jurnal Ekonomi Syariah, 2025)
Problematic financing or Non-Performing Financing (NPF) is a major challenge in the Islamic banking industry, as it can disrupt operational stability and reduce public trust in Islamic financial institutions. This study aims to analyze the strategies and effectiveness of handling problematic financing at Bank Sumsel Babel Capem Muara Kelingi. A descriptive qualitative approach was employed, with data collected through direct observation, interviews, and documentation during the author's internship. The findings indicate that NPF management is carried out through two main approaches: preventive and curative. Preventive efforts include financing feasibility analysis and customer education, while curative measures involve restructuring, renegotiation, and collateral execution. Additionally, the utilization of collateral and financing recovery programs are implemented with a prudential approach, while upholding Islamic values such as justice and mutual consultation. Through these integrated strategies, Bank Sumsel Babel Capem Muara Kelingi can minimize the risk of losses due to NPF and maintain the quality of its financing portfolio